The Best Village Selection Decision Support System at the District Level Using the AHP Method (Case Study at the Pagar Merbau District Office) - Ika Rara Pratiwi (Institute of Computer Science, 2020)
The empowerment of rural communities needs to be done institutional strengthening, increased motivation and self-help in community cooperation, so that in order to assess the success of village development, it is necessary to conduct a targeted, coordinated, integrated and sustainable assessment. with an assessment indicator. Village assessment is best done by comparing the latest development level based on village profile data in accordance with the assessment indicators. This study aims to build a decision support system to determine the best village based on the village assessment score using the Analytic Hierarchy Process (AHP) method. The data used is the village data in the Pagar Merbau sub-district. This best village assessment must pay attention to 6 criteria. The results of the accuracy testing that is performed produce accuracy values ​​from the data output process as much as 5 data. The output of this system is the ranking of each village that has been assessed so as to produce recommendations for decision making in determining the best village.